2022
DOI: 10.1186/s13102-022-00421-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between matrix metalloproteinase-3 gene polymorphisms and tendon-ligament injuries: evidence from a meta-analysis

Abstract: Background Tendon-ligament injuries (TLIs), including Achilles tendinopathy, cruciate ligament injury, tennis elbow, rotator cuff injury, patellar tendinopathy, and tibial tendinopathy, are common musculoskeletal soft injuries during physical activity. Matrix metalloproteinase-3 (MMP-3) gene polymorphisms have been implicated in the etiology of TLIs in several genetic association studies with inconsistent results. The purpose of this study was to collect and synthesize the current evidences on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Due to the applied research model, their results are characterized by high variability resulting from different criteria for selecting the study and control groups, as well as ethnic differences. In the light of current knowledge, well-established factors of susceptibility to tendinopathy are the polymorphic variants of collagen, type I, alpha-1 ( COL1A1 ) [ 33 ], collagen, type V, alpha-1 ( COL5A1 ) [ 34 ] and matrix metalloproteinase 3 ( MMP3 ) [ 35 ] genes. However, little is known about their effect on the prognosis of tennis elbow therapy, as such studies have not been conducted so far.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the applied research model, their results are characterized by high variability resulting from different criteria for selecting the study and control groups, as well as ethnic differences. In the light of current knowledge, well-established factors of susceptibility to tendinopathy are the polymorphic variants of collagen, type I, alpha-1 ( COL1A1 ) [ 33 ], collagen, type V, alpha-1 ( COL5A1 ) [ 34 ] and matrix metalloproteinase 3 ( MMP3 ) [ 35 ] genes. However, little is known about their effect on the prognosis of tennis elbow therapy, as such studies have not been conducted so far.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to MMP-2 and MMP-9, MMP-3 has been found to be dysregulated during tendinopathies, which is inconsistent with its expected role in matrix remodeling. A study also suggested that the expression of MMP-3 is suppressed during tendinopathy, and MMP-3 polymorphism may contribute to chronic tendon disorders [67]. As MMP-3 also plays a crucial role in matrix remodeling, the downregulation or complete inhibition of MMP-3 by TIMP-1 would imply the failure of proper matrix remodeling [68].…”
Section: Regulating the Hypoxic Environment May Promote Tendon Repairmentioning
confidence: 99%
“…Additionally, just as there appear to be genetic markers for good outcomes after rupture of tendons such as the Achilles and rotator cuff tendons, genetic risk for tearing/rupturing such tendons has also been reported (116)(117)(118)(119)(120)(121)(122)(123). Thus, the biomarkers that are proteins result from gene expression (to variable levels dependent on regulation at the DNA level) while genetic risk for injury is in the genome (DNA and potentially epigenetically modified DNA) but how such genomic risk is translated to risk at the tissue level is still largely unknown.…”
Section: Biomarkers Of Tendon Repair Biomarkers and Achilles Tendon H...mentioning
confidence: 99%
“…Thus, the biomarkers that are proteins result from gene expression (to variable levels dependent on regulation at the DNA level) while genetic risk for injury is in the genome (DNA and potentially epigenetically modified DNA) but how such genomic risk is translated to risk at the tissue level is still largely unknown. While some of these studies are based on risk in twins (123), others have indicated that variations in specific molecules such as MMP-3 (122), iNOS (119), or extracellular matrix genes such as COL1A1 (117) pose risk. Ultimately, there will be a need to integrate the risk factors for injury with those for good and poor healing outcomes to obtain a more complete picture of the landscape in individual patients.…”
Section: Biomarkers Of Tendon Repair Biomarkers and Achilles Tendon H...mentioning
confidence: 99%